Reliability and Validity of ACREDA Drug-Related Locus of Control Scale - Amin Al Haadi Bin Shafie; Nurul Ashikin Binti Ahmat Miskam; Mohd Khairul Anuar Bin Rahimi; Nurhafizah Binti Mohd Sukor; Hishamuddin Abdul Wahab; Mohd Rushdan Mohd Jailani; Siti Nubailah Mohd Yusof (IDOSI Publications, 2024)
Volume 35 Number 11